Cerebral Sinovenous Thrombosis in Children and Neonates: Clinical Experience, Laboratory, Treatment, and Outcome. (November 2015) - Bektaş, Ömer; Teber, Serap; Akar, Nejat; Uysal, Leyla Zümrüt; Arsan, Saadet; Atasay, Begüm; Deda, Gülhis
Our aim is to present the etiology and risk factors for cerebral sinovenous thrombosis (CSVT) and the radiological findings, anticoagulant therapy used, and treatment outcome of patients with CSVT. This study included 12 patients who were treated for CSVT at the Ankara University, School of Medicine, Department of Pediatric Neurology. This study included 5 girls (41.7%) and 7 boys (58.3%) with a mean age of symptom onset of 5.2 ± 6.29 years (range: 0-18 years), who were followed at our institution for a mean of 1.8 ± 1.73 years (range: 0-6.5 years). Among the patients, 3 had no risk factors, 2 had 1 risk factor, and 7 had multiple risk factors. Anticoagulant therapy was administered to 4 patients, of which 1 had neurological sequelae; neurological sequelae or exitus occurred in 4 of the 8 patients who did not receive anticoagulant therapy. The present findings showed that appropriate prophylaxis in appropriately selected patients reduced the rate of recurrence of CSVT.